Percutaneous screw fixation and external stabilization as definitive surgical intervention for a pelvic ring injury combined with an acetabular fracture in the acute phase of polytrauma in Korea: a case report - Hohyoung Lee; Myung-Rae Cho; Suk-Kyoon Song; Euisun Yoon; Sungho Lee (Journal of Trauma and Injury)
Unstable pelvic ring injuries are potentially life-threatening and associated with high mortality and complication rates in polytrauma patients. The most common cause of death in patients with pelvic ring injuries is massive bleeding. With resuscitation, external fixation can be performed as a temporary stabilization procedure for hemostasis in unstable pelvic fractures. Internal fixation following temporary external fixation of the pelvic ring yields superior and more reliable stabilization. However, a time-consuming extended approach to open reduction and internal fixation of the pelvic ring is frequently precluded by an unacceptable physiologic condition and/or concomitant injuries in patients with multiple injuries. Conservative treatment may lead to pelvic ring deformity, which is associated with various functional disabilities such as limb length discrepancy, gait disturbance, and sitting intolerance. Therefore, if the patient is not expected to be suitable for additional surgery due to a poor expected physiologic condition, definitive external fixation in combination with various percutaneous screw fixations to restore the pelvic ring should be considered in the acute phase. Herein, we report a case of unstable pelvic ring injury successfully treated with definitive external fixation and percutaneous screw fixation in the acute phase in a severely injured polytrauma patient.